GAME TECHNOLOGIES IN THE WORK OF SOCIAL WORKERS - Sanzharovets, Valentina; Petrenko, Tetyana; Novikova , Natalia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
Social work, as a field of activity, is focused on improving the quality of life of people who find themselves in difficult life situations. This is a wide range of actions aimed at supporting, counseling and helping different population groups to overcome difficulties and achieve social adaptation. In today’s world, in the context of growing social problems and needs, gaming technologies remain a necessary tool for providing assistance to various categories of social work clients. Ability to create interactive and adaptive approaches to improve work efficiency and provide better services by social workers. From the perspective of social work, the variety of games becomes a powerful tool to achieve different goals in working with clients. Games are used as a means of increasing the effectiveness of interaction and promoting the development of various aspects of the personality.